Disputed climate science in the media: Do countries matter?. (February 2014) - Grundmann, Reiner; Scott, Mike
This article presents findings from a large-scale newspaper analysis of climate change discourses in four developed countries, using corpus linguistics methodology. We map the discourse over time, showing peaks and troughs of attention and explaining their causes. Different connotations of common terms such as global warming and climate change in different countries are analysed. Cluster and key-word analysis show the relative salience of specific words and word combinations during crucial periods. We identify main claims makers and the relative visibility of advocates and sceptics. The main finding is that former are far more prominent in all countries. We also look at the coverage of 'climategate'. Finally, we make reference to existing theoretical frameworks.